Uncertain diagnosis and prognosis in advanced melanoma: a qualitative study of the experiences of bereaved carers in a time of immune and targeted therapies. (21st February 2019) - Fox, J.A.; Langbecker, D.; Rosenberg, J.; Ekberg, S.
Summary: Background: Recent advances in advanced melanoma therapies are associated with improved survival for some patients. However, how patients with diagnoses of advanced disease and their carers experience this expanding treatment paradigm is not well understood. Objectives: To explore bereaved carers' accounts of the trajectory of advanced melanoma involving treatment by immune or targeted therapies, to build an understanding of their experiences of care relating to diagnosis and prognosis. Methods: A qualitative exploratory design, using methods drawn from grounded theory, was adopted. Analyses drew on in‐depth interviews with 20 bereaved carers from three metropolitan melanoma treatment centres in Australia. A flexible interview guide and structured approach to concurrent data collection and analysis were applied. Results: Carers described qualities of the experience, including the shock of diagnosis after a sometimes‐innocuous presentation with vague symptoms. They reported an unclear prognosis with complexity arising from interplay between an uncertain disease trajectory and often ambiguous expectations of outcomes of emerging immune and targeted therapies. Uncertainty dominated carers' experiences, increasing the complexity of care planning. Conclusions: Effective communication of an advanced melanoma diagnosis and prognosis is critical. Recognition of the uncertainty inherent in the benefit of immune and targeted therapies in a constructive manner may facilitate more timely and effective care‐planning conversations between patients, carers and medical specialists. Abstract : What's already known about this topic? Historically, patients with advanced melanoma had a very poor prognosis, with limited treatment options. Recent advances in melanoma therapies such as immune and targeted therapies show promise regarding prolonged survival for a subset of patients. Currently, the impact of diagnosis and uncertain prognosis on patients and carers is unclear. What does this study add? This study is among the first to explore bereaved carers' experiences within the immune and targeted therapy treatment paradigms, and builds understanding from this perspective. This study explores the influence of uncertainty on patient and carer experience. Managing expectations of immune and targeted therapies is essential. What are the clinical implications of the work? Early and ongoing assessment of patient and carer preference for and understanding of diagnostic and prognostic information is essential. Medical specialists must clarify and tailor information to patients' and carers' needs and preferences as the disease progresses. Active, constructive recognition of the uncertain benefit of new therapies may facilitate more timely and effective care‐planning conversations between patients, carers and medical professionals. Linked Editorial:  Nelson et al. Br J Dermatol 2019; 180 :1271–1273 . Plain language summary available online Respond to this article